Dissulfeto de molibdênio esfoliado micromecanicamente depositado em fibra óptica para geração de pulsos ultracurtos - Aiub, Eduardo José (2016)
In this work, we describe the characterization, transfer process and fabrication of mechanically exfoliated MoS2 (molybdenum disulfide) samples deposited on the fiber facet and D-shaped fiber. The characterization of these samples was made through Raman spectroscopy, making a mapping of the samples and analyzing the frequency difference between the vibrational modes E2g e A1g, it is possible to determine the number of layers to be transferred. Also, it was required to prepare a layered substrate of PVA (polyvinyl alcohol) and PMMA (Polymethyl- methacrylate), so that it was possible to remove the nanomaterial from the glass substrate and deposit it on another surface. Furthermore, it was performed control and alignment of the material with the core of the fiber, using a stage XYZ and an optical microscope (10X lens). An application for the fabricated samples was demonstrated through the generation of ultrashort pulses in EDFL (Erbium-doped fiber lasers) and YDFL (Ytterbium-doped fiber lasers) using them as saturable absorbers. The best results obtained were a pulse duration of 810 femtoseconds and bandwidth of 4.09 nm using mechanically exfoliated MoS2 on the fiber facet and pulse duration of 200 fs and bandwidth of 20,5 nm on the D-shaped fiber. In the samples on the fiber facet was the presence of NPR (Nonlinear Polarization Rotation) resulting in a hybrid effect. Results of ultrashort pulses with mechanically exfoliated MoS2 have not yet been reported in the literature.